2013
DOI: 10.1097/eja.0b013e3283607827
|View full text |Cite
|
Sign up to set email alerts
|

Chlorhexidine to maintain cleanliness of laryngoscope handles

Abstract: Decontamination with Sani-Cloth CHG 2% wipes confers additional advantages over routine autoclaving or handle disposal, due to a residual effect. Autoclaving handles may be desirable on a scheduled basis and if Clostridium difficile is encountered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 10 publications
0
26
0
1
Order By: Relevance
“…The contamination rates from previous studies since 2008 [12,16,17,19-21], when the US CDC suggested disinfection instructions, were 42.0 to 57.3% of laryngoscope blades and 69.2 to 86.0% of handles. These values were more than those of the present study were, and this result may be caused by differences in each institution’s disinfection instructions, specimen collection method, sample delivery, culture method, and type of department that used a laryngoscope.…”
Section: Discussionmentioning
confidence: 97%
“…The contamination rates from previous studies since 2008 [12,16,17,19-21], when the US CDC suggested disinfection instructions, were 42.0 to 57.3% of laryngoscope blades and 69.2 to 86.0% of handles. These values were more than those of the present study were, and this result may be caused by differences in each institution’s disinfection instructions, specimen collection method, sample delivery, culture method, and type of department that used a laryngoscope.…”
Section: Discussionmentioning
confidence: 97%
“…Howell et al conducted an audit, three laboratory comparative studies, and a repeat audit to establish an effective cleaning regimen for laryngoscope handles. In the audit, the researchers obtained microbiological cultures from 55 patient‐ready laryngoscope handles in the operating suites, neonatal intensive care unit, and emergency department of a hospital in the United Kingdom.…”
Section: Resultsmentioning
confidence: 99%
“…The researchers found no growth on 32 (58.0%) of the laryngoscope handles, one species of bacteria on 14 (26.0%) of the handles, and two species of bacteria on 9 (16.0%) of the handles. The researchers identified the bacteria as coagulase‐negative staphylococci, Corynebacterium species, Bacillus species, and Pseudomonas aeruginosa …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have demonstrated that contamination of laryngoscope blades and handles is common. [252627] The fact that knurled handles of laryngoscopes also get contaminated is often overlooked by most of us. Handles should be washed, disinfected and if suitable, sterilised after every use.…”
Section: Individual Item Considerationmentioning
confidence: 99%